Pengaruh Motivasi Kerja Dan Budaya Organisasi Terhadap Produktivitas Kerja Karyawan Pada PT Natura Indoland - Febrian Dini; Andi Heru Susanto (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
This study aims to determine the influence of work motivation and organizational culture on the work productivity of PT Natura Indoland employees. The approach used was quantitative, the research design was associative with a total of 95 respondents. The research instrument uses questionnaire distribution, in data analysis using several tests conducted using the SPSS program. The result of the analysis is known that work motivation has no effect on work productivity with a magnitude of -1.71% influence, while organizational culture has an influence on work productivity with a magnitude of 27,56% and a large influence of the two variables X on Y of 66,3%. As a company, we must pay more attention to work motivation and organizational culture in the company so that employee work productivity is maintained.